Goff, Nemaha County - Hermesch, Jessica (Kansas State University, The Chapman Center for Rural Studies, 2013)
This study illustrates the founding, growth, and decline of the small town of Goff, Kansas in Nemaha County. Originally located at the crossroads of the Central Branch of the Missouri Pacific Railroad and the Kansas City, Wyandotte and Northwestern Railroad, the town once ran the largest industry in the county. This study includes an interview, early plat maps of the town, and photographs of early and present-day Goff.
Jessica Hermesch, “Goff, Nemaha County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/126.
Keywords: Edward H. Goff; Goff; Harrison Township; Nemaha County; Missouri Pacific Railroad; Spring Creek